Challenges of Diagnosing Primary Ewing’s Sarcoma in the Small Intestine of the Elderly: A Case Report - Yang, Jianchuan; Wei, Hong; Lin, Yucheng; Lin, Ning; Wu, Songsong; Yu, Xunbin (Frontiers in Oncology, 2021)
Extraosseous Ewing's sarcoma (EES) is a malignant tumor that is classified as a rare disease. EES is common in children and adolescents with a rarer incidence being present in the elderly. It is easier to diagnose Ewing's sarcoma (ES) occurring in the bone since it is related to the bone and has obvious swollen growth that appears in imaging. ES in other organs often leads to misdiagnosis due to different imaging manifestations. ES of the primary intestine is rare, with only a few reports described in the literature. Here we report a case of a 69-year-old Chinese male patient who was experiencing abdominal pain for over 3 months. Ultrasonography (US) revealed that the left lower abdomen contained a solid hypoechoic lesion with irregular multiple ulcers and extension to the dome of bladder. Contrast-enhanced ultrasonography (CEUS) showed that the lesion contained heterogeneous enhancement，quick peripheral enhanced tissue washout and was considered as a malignant tumor. Abdominal CT showed an abnormal density of the pelvic cavity that was considered as an intestine large diverticulum with an abscess. PET-CT showed a high metabolic mass in the lower abdomen above the bladder, multiple metabolic nodules in the mesentery, considered as small intestinal stromal tumor with lymph nodes metastasis and that a diagnosis of lymphoma should be excluded. Gastric and endoscopy examinations showed no obvious occupying lesions when performed at another hospital 1 month prior. The final postoperative pathology confirmed ES of the small intestine.